Influences of Curing Environment on Strength Performances of Shanghai Clayey Soil Reinforced with Palm Fiber - Jili Qu; Kun Xiong (Advances in Civil Engineering)
Owing to its environment-friendly, economically available, and sustainable property, the palm fiber was attempted to improve the quality of Shanghai clayey soil together with lime. The direct shear tests (DST), ultrasonic pulse velocity tests (UPV), and the unconfined compressive tests (UCT) have been carried out on soils mixed with palm fiber and lime under 3 curing conditions of immersion in water, cyclic wetting-drying, and air curing at a series of contents of additives. The corresponding indexes of shear strength (τ), cohesion (c), internal friction angle (φ), initial shear modulus (G0), and unconfined compressive strength (qu) were obtained and analyzed. Results show that immersed-in-water environment is optimum for the formation of shear strength, initial shear modulus, cohesion, and unconfined compressive strength (UCS), while the air curing condition is the worst for admixture treated soil. Lime can increase G0, but palm fiber can slightly reduce G0. Lime has significant effect on increase of internal friction angle; on the contrary, palm fiber has only limited effect. c/G0 for any type of sample remains almost constant under different curing conditions. It demonstrates that c and G0 possess the comparative development trend under different curing environment.